(x-4)(x-3)(x-2+3i)(x+2+3i)=0

Simple and best practice solution for (x-4)(x-3)(x-2+3i)(x+2+3i)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-4)(x-3)(x-2+3i)(x+2+3i)=0 equation:


Simplifying
(x + -4)(x + -3)(x + -2 + 3i)(x + 2 + 3i) = 0

Reorder the terms:
(-4 + x)(x + -3)(x + -2 + 3i)(x + 2 + 3i) = 0

Reorder the terms:
(-4 + x)(-3 + x)(x + -2 + 3i)(x + 2 + 3i) = 0

Reorder the terms:
(-4 + x)(-3 + x)(-2 + 3i + x)(x + 2 + 3i) = 0

Reorder the terms:
(-4 + x)(-3 + x)(-2 + 3i + x)(2 + 3i + x) = 0

Multiply (-4 + x) * (-3 + x)
(-4(-3 + x) + x(-3 + x))(-2 + 3i + x)(2 + 3i + x) = 0
((-3 * -4 + x * -4) + x(-3 + x))(-2 + 3i + x)(2 + 3i + x) = 0
((12 + -4x) + x(-3 + x))(-2 + 3i + x)(2 + 3i + x) = 0
(12 + -4x + (-3 * x + x * x))(-2 + 3i + x)(2 + 3i + x) = 0
(12 + -4x + (-3x + x2))(-2 + 3i + x)(2 + 3i + x) = 0

Combine like terms: -4x + -3x = -7x
(12 + -7x + x2)(-2 + 3i + x)(2 + 3i + x) = 0

Multiply (12 + -7x + x2) * (-2 + 3i + x)
(12(-2 + 3i + x) + -7x * (-2 + 3i + x) + x2(-2 + 3i + x))(2 + 3i + x) = 0
((-2 * 12 + 3i * 12 + x * 12) + -7x * (-2 + 3i + x) + x2(-2 + 3i + x))(2 + 3i + x) = 0
((-24 + 36i + 12x) + -7x * (-2 + 3i + x) + x2(-2 + 3i + x))(2 + 3i + x) = 0
(-24 + 36i + 12x + (-2 * -7x + 3i * -7x + x * -7x) + x2(-2 + 3i + x))(2 + 3i + x) = 0

Reorder the terms:
(-24 + 36i + 12x + (-21ix + 14x + -7x2) + x2(-2 + 3i + x))(2 + 3i + x) = 0
(-24 + 36i + 12x + (-21ix + 14x + -7x2) + x2(-2 + 3i + x))(2 + 3i + x) = 0
(-24 + 36i + 12x + -21ix + 14x + -7x2 + (-2 * x2 + 3i * x2 + x * x2))(2 + 3i + x) = 0

Reorder the terms:
(-24 + 36i + 12x + -21ix + 14x + -7x2 + (3ix2 + -2x2 + x3))(2 + 3i + x) = 0
(-24 + 36i + 12x + -21ix + 14x + -7x2 + (3ix2 + -2x2 + x3))(2 + 3i + x) = 0

Reorder the terms:
(-24 + 36i + -21ix + 3ix2 + 12x + 14x + -7x2 + -2x2 + x3)(2 + 3i + x) = 0

Combine like terms: 12x + 14x = 26x
(-24 + 36i + -21ix + 3ix2 + 26x + -7x2 + -2x2 + x3)(2 + 3i + x) = 0

Combine like terms: -7x2 + -2x2 = -9x2
(-24 + 36i + -21ix + 3ix2 + 26x + -9x2 + x3)(2 + 3i + x) = 0

Multiply (-24 + 36i + -21ix + 3ix2 + 26x + -9x2 + x3) * (2 + 3i + x)
(-24(2 + 3i + x) + 36i * (2 + 3i + x) + -21ix * (2 + 3i + x) + 3ix2 * (2 + 3i + x) + 26x * (2 + 3i + x) + -9x2 * (2 + 3i + x) + x3(2 + 3i + x)) = 0
((2 * -24 + 3i * -24 + x * -24) + 36i * (2 + 3i + x) + -21ix * (2 + 3i + x) + 3ix2 * (2 + 3i + x) + 26x * (2 + 3i + x) + -9x2 * (2 + 3i + x) + x3(2 + 3i + x)) = 0
((-48 + -72i + -24x) + 36i * (2 + 3i + x) + -21ix * (2 + 3i + x) + 3ix2 * (2 + 3i + x) + 26x * (2 + 3i + x) + -9x2 * (2 + 3i + x) + x3(2 + 3i + x)) = 0
(-48 + -72i + -24x + (2 * 36i + 3i * 36i + x * 36i) + -21ix * (2 + 3i + x) + 3ix2 * (2 + 3i + x) + 26x * (2 + 3i + x) + -9x2 * (2 + 3i + x) + x3(2 + 3i + x)) = 0

Reorder the terms:
(-48 + -72i + -24x + (72i + 36ix + 108i2) + -21ix * (2 + 3i + x) + 3ix2 * (2 + 3i + x) + 26x * (2 + 3i + x) + -9x2 * (2 + 3i + x) + x3(2 + 3i + x)) = 0
(-48 + -72i + -24x + (72i + 36ix + 108i2) + -21ix * (2 + 3i + x) + 3ix2 * (2 + 3i + x) + 26x * (2 + 3i + x) + -9x2 * (2 + 3i + x) + x3(2 + 3i + x)) = 0
(-48 + -72i + -24x + 72i + 36ix + 108i2 + (2 * -21ix + 3i * -21ix + x * -21ix) + 3ix2 * (2 + 3i + x) + 26x * (2 + 3i + x) + -9x2 * (2 + 3i + x) + x3(2 + 3i + x)) = 0

Reorder the terms:
(-48 + -72i + -24x + 72i + 36ix + 108i2 + (-42ix + -21ix2 + -63i2x) + 3ix2 * (2 + 3i + x) + 26x * (2 + 3i + x) + -9x2 * (2 + 3i + x) + x3(2 + 3i + x)) = 0
(-48 + -72i + -24x + 72i + 36ix + 108i2 + (-42ix + -21ix2 + -63i2x) + 3ix2 * (2 + 3i + x) + 26x * (2 + 3i + x) + -9x2 * (2 + 3i + x) + x3(2 + 3i + x)) = 0
(-48 + -72i + -24x + 72i + 36ix + 108i2 + -42ix + -21ix2 + -63i2x + (2 * 3ix2 + 3i * 3ix2 + x * 3ix2) + 26x * (2 + 3i + x) + -9x2 * (2 + 3i + x) + x3(2 + 3i + x)) = 0

Reorder the terms:
(-48 + -72i + -24x + 72i + 36ix + 108i2 + -42ix + -21ix2 + -63i2x + (6ix2 + 3ix3 + 9i2x2) + 26x * (2 + 3i + x) + -9x2 * (2 + 3i + x) + x3(2 + 3i + x)) = 0
(-48 + -72i + -24x + 72i + 36ix + 108i2 + -42ix + -21ix2 + -63i2x + (6ix2 + 3ix3 + 9i2x2) + 26x * (2 + 3i + x) + -9x2 * (2 + 3i + x) + x3(2 + 3i + x)) = 0
(-48 + -72i + -24x + 72i + 36ix + 108i2 + -42ix + -21ix2 + -63i2x + 6ix2 + 3ix3 + 9i2x2 + (2 * 26x + 3i * 26x + x * 26x) + -9x2 * (2 + 3i + x) + x3(2 + 3i + x)) = 0

Reorder the terms:
(-48 + -72i + -24x + 72i + 36ix + 108i2 + -42ix + -21ix2 + -63i2x + 6ix2 + 3ix3 + 9i2x2 + (78ix + 52x + 26x2) + -9x2 * (2 + 3i + x) + x3(2 + 3i + x)) = 0
(-48 + -72i + -24x + 72i + 36ix + 108i2 + -42ix + -21ix2 + -63i2x + 6ix2 + 3ix3 + 9i2x2 + (78ix + 52x + 26x2) + -9x2 * (2 + 3i + x) + x3(2 + 3i + x)) = 0
(-48 + -72i + -24x + 72i + 36ix + 108i2 + -42ix + -21ix2 + -63i2x + 6ix2 + 3ix3 + 9i2x2 + 78ix + 52x + 26x2 + (2 * -9x2 + 3i * -9x2 + x * -9x2) + x3(2 + 3i + x)) = 0

Reorder the terms:
(-48 + -72i + -24x + 72i + 36ix + 108i2 + -42ix + -21ix2 + -63i2x + 6ix2 + 3ix3 + 9i2x2 + 78ix + 52x + 26x2 + (-27ix2 + -18x2 + -9x3) + x3(2 + 3i + x)) = 0
(-48 + -72i + -24x + 72i + 36ix + 108i2 + -42ix + -21ix2 + -63i2x + 6ix2 + 3ix3 + 9i2x2 + 78ix + 52x + 26x2 + (-27ix2 + -18x2 + -9x3) + x3(2 + 3i + x)) = 0
(-48 + -72i + -24x + 72i + 36ix + 108i2 + -42ix + -21ix2 + -63i2x + 6ix2 + 3ix3 + 9i2x2 + 78ix + 52x + 26x2 + -27ix2 + -18x2 + -9x3 + (2 * x3 + 3i * x3 + x * x3)) = 0

Reorder the terms:
(-48 + -72i + -24x + 72i + 36ix + 108i2 + -42ix + -21ix2 + -63i2x + 6ix2 + 3ix3 + 9i2x2 + 78ix + 52x + 26x2 + -27ix2 + -18x2 + -9x3 + (3ix3 + 2x3 + x4)) = 0
(-48 + -72i + -24x + 72i + 36ix + 108i2 + -42ix + -21ix2 + -63i2x + 6ix2 + 3ix3 + 9i2x2 + 78ix + 52x + 26x2 + -27ix2 + -18x2 + -9x3 + (3ix3 + 2x3 + x4)) = 0

Reorder the terms:
(-48 + -72i + 72i + 36ix + -42ix + 78ix + -21ix2 + 6ix2 + -27ix2 + 3ix3 + 3ix3 + 108i2 + -63i2x + 9i2x2 + -24x + 52x + 26x2 + -18x2 + -9x3 + 2x3 + x4) = 0

Combine like terms: -72i + 72i = 0
(-48 + 0 + 36ix + -42ix + 78ix + -21ix2 + 6ix2 + -27ix2 + 3ix3 + 3ix3 + 108i2 + -63i2x + 9i2x2 + -24x + 52x + 26x2 + -18x2 + -9x3 + 2x3 + x4) = 0
(-48 + 36ix + -42ix + 78ix + -21ix2 + 6ix2 + -27ix2 + 3ix3 + 3ix3 + 108i2 + -63i2x + 9i2x2 + -24x + 52x + 26x2 + -18x2 + -9x3 + 2x3 + x4) = 0

Combine like terms: 36ix + -42ix = -6ix
(-48 + -6ix + 78ix + -21ix2 + 6ix2 + -27ix2 + 3ix3 + 3ix3 + 108i2 + -63i2x + 9i2x2 + -24x + 52x + 26x2 + -18x2 + -9x3 + 2x3 + x4) = 0

Combine like terms: -6ix + 78ix = 72ix
(-48 + 72ix + -21ix2 + 6ix2 + -27ix2 + 3ix3 + 3ix3 + 108i2 + -63i2x + 9i2x2 + -24x + 52x + 26x2 + -18x2 + -9x3 + 2x3 + x4) = 0

Combine like terms: -21ix2 + 6ix2 = -15ix2
(-48 + 72ix + -15ix2 + -27ix2 + 3ix3 + 3ix3 + 108i2 + -63i2x + 9i2x2 + -24x + 52x + 26x2 + -18x2 + -9x3 + 2x3 + x4) = 0

Combine like terms: -15ix2 + -27ix2 = -42ix2
(-48 + 72ix + -42ix2 + 3ix3 + 3ix3 + 108i2 + -63i2x + 9i2x2 + -24x + 52x + 26x2 + -18x2 + -9x3 + 2x3 + x4) = 0

Combine like terms: 3ix3 + 3ix3 = 6ix3
(-48 + 72ix + -42ix2 + 6ix3 + 108i2 + -63i2x + 9i2x2 + -24x + 52x + 26x2 + -18x2 + -9x3 + 2x3 + x4) = 0

Combine like terms: -24x + 52x = 28x
(-48 + 72ix + -42ix2 + 6ix3 + 108i2 + -63i2x + 9i2x2 + 28x + 26x2 + -18x2 + -9x3 + 2x3 + x4) = 0

Combine like terms: 26x2 + -18x2 = 8x2
(-48 + 72ix + -42ix2 + 6ix3 + 108i2 + -63i2x + 9i2x2 + 28x + 8x2 + -9x3 + 2x3 + x4) = 0

Combine like terms: -9x3 + 2x3 = -7x3
(-48 + 72ix + -42ix2 + 6ix3 + 108i2 + -63i2x + 9i2x2 + 28x + 8x2 + -7x3 + x4) = 0

Solving
-48 + 72ix + -42ix2 + 6ix3 + 108i2 + -63i2x + 9i2x2 + 28x + 8x2 + -7x3 + x4 = 0

Solving for variable 'i'.

The solution to this equation could not be determined.

See similar equations:

| 2(2x+110)+2x=300 | | 2(x+3)+5x= | | 2y=-7x+12 | | (2x+17)=(8x-13) | | X^3-8x^2=-12x | | 11n-6-10n-1=8 | | (X+5)=14 | | 6x-2x-25=31 | | 6x-2x-25=32 | | d/3-10=2 | | x^2+9x-54=0equation | | 231=-7(-4n-1) | | 2y-20=180 | | K+14=19 | | 2x-6=10.5 | | (3x-2)(x-8)=0 | | k/7=9/7 | | 6m+19=7m+9 | | -1/4y-16 | | 4x^2+24=20x | | 6y=-2x+12 | | 2x+7y-5=0 | | 9c+4=2c-3 | | 11x-5-7x= | | -1/4-16 | | y+y+3/2=3 | | 2(x+7)+3x-5=24 | | 17-4n=-7(1-2n)+6 | | 3cospiX=1 | | A=18-5ln(42-L) | | x+11+x+5+2x-4+2x=540 | | 20=18-5ln(42-L) |

Equations solver categories